Twenty-nine cases of resection of suprasellar meningioma through small bone window: an interhemispheric approach - Lu, Zhao-Feng; Cheng, Xiao-bing; Zhao, Yong-gang; Shi, Bao-Zhong (Contemporary Oncology/Współczesna Onkologia, 2013)
Aim of the study : The present study aims to discuss the value and the effect of resection of suprasellar meningioma through the interhemispheric approach. Material and methods : Twenty-nine cases of patients with suprasellar meningioma diagnosed through enhanced magnetic resonance imaging (MRI) scans and postoperative histopathological examination underwent resection of tumours (the largest diameter ranged from 3 cm to 6 cm) by the microsurgical technique of a small bone window (about 4 cm × 5 cm) through the interhemispheric approach. Results: Among all cases, 25 (86%) (Simpson I, II) were of total resection of tumours and 4 were of subtotal resection of tumours. 19 (65%) were of improvement of vision and visual field, 2 (7%) were of postoperative diabetes insipidus, and 1 (3%) was of electrolyte imbalance. No operative death occurred. Conclusions : The small bone window interhemispheric approach can be used to expose tumours, lightly stretch brain tissues, reduce the incidence of complications, and improve the total resection rate of tumours of patients with sellae meningiomas growing forward, upward, and into the sella.